Gas Separations using Nanoporous Atomically Thin Membranes: Recent Theoretical, Simulation, and Experimental Advances. Issue 32 (19th June 2022) - Yuan, Zhe; He, Guangwei; Li, Sylvia Xin; Misra, Rahul Prasanna; Strano, Michael S.; Blankschtein, Daniel
Abstract: Porous graphene and other atomically thin 2D materials are regarded as highly promising membrane materials for high‐performance gas separations due to their atomic thickness, large‐scale synthesizability, excellent mechanical strength, and chemical stability. When these atomically thin materials contain a high areal density of gas‐sieving nanoscale pores, they can exhibit both high gas permeances and high selectivities, which is beneficial for reducing the cost of gas‐separation processes. Here, recent modeling and experimental advances in nanoporous atomically thin membranes for gas separations is discussed. The major challenges involved, including controlling pore size distributions, scaling up the membrane area, and matching theory with experimental results, are also highlighted. Finally, important future directions are proposed for real gas‐separation applications of nanoporous atomically thin membranes. Abstract : The recent development of novel atomically thin 2D materials, including graphene, hexagonal boron nitride, and transition metal dichalcogenides, offers great opportunities for potential breakthroughs in the membrane separation field. Recent research advances, challenges, and potential future directions in the application of nanoporous atomically thin membranes for gas separation are summarized.